Cold light - Mohtarrudin, Norhafizah; O. K. Rahmat, Rahmita Wirza; Md Isa, Muhd Adli; Mahayidin, Hasni; Ng, Seng Beng; Baharuddin, Mohd Nasir (Universiti Putra Malaysia Press, 2017)
Fireflies are winged beetles that emit light to attract mates or prey. Fireflies produce a ‘cold light’ that glows and light up the darkness especially in the forest. They use bioluminescence without infrared or ultraviolet frequencies during evening twilight.